Islamic perspectives on the use of blood plasma in cosmetics: jurisprudential analysis and contemporary challenges - Anisha Emilia Redzuan; Mohd Izhar Ariff Mohd Kashim (Penerbit Universiti Kebangsaan Malaysia, 2025)
This study examines the permissibility of cosmetics derived from blood plasma from an Islamic legal perspective, addressing theological and legal debates arising from the classification of blood as impure under Islamic law. It focuses on the key jurisprudential principles of ritual purity (ṭahārah), transformation (istiḥālah), and necessity (ḍarūrah). Utilizing a qualitative library-based research approach and content analysis, the study engages with the Qurʾān, Hadith, classical fiqh compendia from the four major Sunni schools (Ḥanafī, Mālikī, Shāfiʿī, and Ḥanbalī), as well as contemporary fatwas issued by recognized Southeast Asian institutions such as JAKIM (Malaysia) and MUI (Indonesia). Selection criteria prioritized jurisprudential relevance, legal edicts, and supporting scientific literature. The analysis identifies recurring themes and jurisprudential arguments surrounding the use of blood plasma in cosmetic products. The findings suggest that classical Islamic jurisprudence generally deems the inclusion of blood in cosmetics impermissible. Although the principle of istiḥālah could potentially render an impure substance permissible, leading contemporary authorities maintain a conservative stance, permitting such substances primarily in cases of medical necessity where no ḥalāl alternatives are available—but not for purposes of beautification. Furthermore, there is no scholarly consensus regarding the sufficiency of transformation processes in topical (cosmetic) applications. This study provides a focused examination of contemporary fatwas from Southeast Asian Islamic bodies, addressing an area that remains relatively underexplored within Islamic bioethics and jurisprudence. It highlights a growing disconnect between rapid biotechnological advancements and the availability of clear, authoritative Islamic rulings, underscoring the urgency for standardized ḥalāl certification and increased consumer education. The prevailing juristic view advises against the use of such cosmetics— particularly those derived from human or non-ḥalāl animal sources—unless full transformation is conclusively established. This research offers a synthesized perspective bridging classical jurisprudence and modern regulatory considerations, thereby contributing to a more coherent framework for evaluating emerging cosmetic technologies through an Islamic legal lens.